Inclined to see it your way: Do altercentric intrusion effects in visual perspective taking reflect an intrinsically social process?. Issue 10 (October 2015) - Nielsen, Maria Kragh; Slade, Lance; Levy, Joseph P.; Holmes, Amanda
It has been suggested that some aspects of mental state understanding recruit a rudimentary, but fast and efficient, processing system, demonstrated by the obligatory slowing down of judgements about what the self can see when this is incongruent with what another can see. We tested the social nature of this system by investigating to what extent these altercentric intrusions are elicited under conditions that differed in their social relevance and, further, how these related to self-reported social perspective taking and empathy. In Experiment 1, adult participants were asked to make "self" or "other" perspective-taking judgements during congruent ("self" and "other" can see the same items) or incongruent conditions ("self" and "other" cannot see the same items) in conditions that were social (i.e., involving a social agent), semisocial (an arrow), or nonsocial (a dual-coloured block). Reaction time indices of altercentric intrusion effects were present across all conditions, but were significantly stronger for the social than for the less social conditions. Self-reported perspective taking and empathy correlated with altercentric intrusion effects in the social condition only. In Experiment 2, the significant correlations for the social condition were replicated, but this time with gaze duration indices of altercentric intrusion effects. Findings are discussed with regard to the degree to which this rudimentary system is socially specialized and how it is linked to more conceptual understanding.